2014
DOI: 10.1186/1471-2474-15-263
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of combined bracing and exercise in adolescent idiopathic scoliosis based on SRS and SOSORT criteria: a prospective study

Abstract: BackgroundRecently an RCT confirmed brace efficacy in adolescent idiopathic scoliosis (AIS) patients. Previously, a Cochrane review suggested also producing studies according to the Scoliosis Research Society (SRS) criteria on the effectiveness of bracing for AIS. Even if the SRS criteria propose a prospective design, until now only one out of 6 published studies was prospective. Our purpose was to evaluate the effects of bracing plus exercises following the SRS and the international Society on Scoliosis Ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 31 publications
3
55
0
6
Order By: Relevance
“…Pod czas gdy sko lio zę I stop nia mo że my le czyć ró żny mi me to da mi fi zjo te ra pii czy re ha bi li ta cji, to od II stop nia (25-45 stop ni wg Cob ba) po win ni śmy za stoso wać gor set or to pe dycz ny do le cze nia sko lioz. Jest to naj sku tecz niej sza, udo ku men to wa na ba da nia mi na u ko wy mi me to da le cze nia nie ope ra cyj ne go idiopa tycz nej sko lio zy mło dzień czej [2][3][4][5][6]. Ko ry go wa nie sko lioz spo so ba mi nie ope ra cyj ny mi i ope ra cyj ny mi po win no być trój płasz czy zno we i uwzględ niać od tworze nie fi zjo lo gicz nej ki fo zy pier sio wej [7].…”
Section: Wstępunclassified
See 2 more Smart Citations
“…Pod czas gdy sko lio zę I stop nia mo że my le czyć ró żny mi me to da mi fi zjo te ra pii czy re ha bi li ta cji, to od II stop nia (25-45 stop ni wg Cob ba) po win ni śmy za stoso wać gor set or to pe dycz ny do le cze nia sko lioz. Jest to naj sku tecz niej sza, udo ku men to wa na ba da nia mi na u ko wy mi me to da le cze nia nie ope ra cyj ne go idiopa tycz nej sko lio zy mło dzień czej [2][3][4][5][6]. Ko ry go wa nie sko lioz spo so ba mi nie ope ra cyj ny mi i ope ra cyj ny mi po win no być trój płasz czy zno we i uwzględ niać od tworze nie fi zjo lo gicz nej ki fo zy pier sio wej [7].…”
Section: Wstępunclassified
“…Ko ry go wa nie sko lioz spo so ba mi nie ope ra cyj ny mi i ope ra cyj ny mi po win no być trój płasz czy zno we i uwzględ niać od tworze nie fi zjo lo gicz nej ki fo zy pier sio wej [7]. Głów nym ce lem le cze nia gor se tem, no szo nym we dług kla sycznych za le ceń 18-23 h/do bę, jest za po bie ga nie pro gresji i po głę bia nia się ist nie ją ce go skrzy wie nia oraz od da le nie per spek ty wy cię żkiej i dość skom pli ko wanej ope ra cji [6,8]. Le cze nie uwa ża się za za koń czo ne z chwi lą osią gnię cia doj rza ło ści kost nej krę go słu pa. Klu czo wym czyn ni kiem, wa run ku ją cym suk ces le czenia, jest kon se kwen cja i su mien ność w no sze niu gor setu [8,9].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…The effectiveness of brace treatment to prevent curve progression has been validated in several studies [4][5][6][7]; moreover, a combination of bracing with PSSE has been shown to decrease spinal deformities and improve quality of life in comparison with bracing alone [1,[7][8][9][10], but adolescents may be disinclined to comply with this enduring therapy. We aimed to examine patients' socio-economic factors and quality of life after fulfilling years of brace treatment combined with PSSE.…”
Section: Introductionmentioning
confidence: 99%
“…The standards involve: observation (mild curves), orthopedic supplies in the form of corrective braces (SRS standards: curve size between 25° and 40°, Risser sign between 0 and 2, and 10 years of age or older) [1,2], and surgical treatment for severe curve, greater than 40° if preventive treatment is unsuccessful [3,4]. An important procedure in preventive treatment, and the only one that is documented, is bracing, the aim of which is to reduce the risk of curve progression in order to avoid surgical procedure [3,5,6].…”
Section: Introductionmentioning
confidence: 99%